PENGARUH PUTUSAN MAHKAMAH KONSTITUSI TERHADAP KEWENANGAN PRESIDEN DALAM PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG - Jumadi, Jumadi; Nuriskandar, Lalu Hendri (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2024)
This research aims to explore the influence of the Constitutional Court (MK) decision on the President's authority in the formation of Government Regulations in Lieu of Laws (Perppu). In the Indonesian constitutional system, Perppu is a legal instrument used by the President to deal with emergencies that require immediate handling, but this authority often gives rise to debate regarding the limits and conditions for its issuance. MK decisions have a crucial role in interpreting and establishing constitutional parameters for the use of this authority, so this research highlights how MK decisions influence the practice of forming Perppu by the President. This research uses normative juridical methods with a conceptual approach and analysis of relevant Constitutional Court decisions, including case studies of decisions that confirm emergency criteria and procedures for issuing Perppu. The findings of this research reveal that the Constitutional Court's decision has strengthened the principle of checks and balances between the executive and legislative branches, by setting stricter limits regarding the conditions that justify the issuance of a Perppu. Apart from that, the Constitutional Court's decision also emphasized the importance of openness and public participation in the Perppu formation process, as an effort to maintain legal accountability and legitimacy in the midst of an emergency situation. Furthermore, this research shows that the Constitutional Court's decision not only limits the President's authority, but also provides clearer guidance regarding the implementation of the Perppu so that it is in line with constitutional values ??and human rights. In the long term, the Constitutional Court's decisions have the potential to encourage reform in the legal regulatory system, by improving the quality of emergency legislation and strengthening protection of democratic principles. Therefore, this research concludes that the Constitutional Court's decision has a significant impact in ensuring that the President's authority in forming Perppu is used proportionally, appropriately, and in accordance with applicable constitutional provisions. Keywords: Constitutional Court Decision, Presidential Authority, Perppu, Constitution, Democracy, Accountability.